Spectral Radius Formulas Involving Generalized Aluthge Transform. (14th March 2022) - Zhang, Zhiqiang; Akram, Muhammad Saeed; Hyder, Javariya; Farid, Ghulam; Yan, Tao
Abstract : In this paper, we aim to develop formulas of spectral radius for an operator S in terms of generalized Aluthge transform, numerical radius, iterated generalized Aluthge transform, and asymptotic behavior of powers of S . These formulas generalize some of the formulas of spectral radius existing in literature. As an application, these formulas are used to obtain several characterizations of normaloid operators.